The name of the rose: classifying 1930s exchange-rate regimes - Urban, S (University of Oxford, 2009)
There is an implicit consensus that 1930s exchange-rate regimes can be characterised as some variant of 'floating'. This paper applies an adaptation of modern methodologies of exchange-rate regime classification to a panel of 47 countries in weekly observations between January 1919 and August 1939. On the basis of modern benchmarks, the 1930s world monetary system would not be considered 'floating' or even 'managed floating'. One implication is that today's fiat-based, managed-floating international financial architecture is unprecedented.